Analysis of fluid pressure, interface stresses and stress intensity factors for layered materials with cracks and inhomogeneities under elastohydrodynamic lubrication contact. (April 2015) - Dong, Qingbing; Zhou, Kun; Wei, Rongbing; Luo, Jun; Srikanth, Narasimalu
Abstract: This study conducts investigations on coated materials with subsurface inhomogeneities and cracks under lubricated contact. The analytical elastic solution of cracked materials with inhomogeneities subjected to elastohydrodynamic lubrication contact is employed by modeling the topmost coating as an inhomogeneity of finite size. The interactions between the loading body, the fluid lubrication film, the coating/substrate system and the subsurface micro-defects within the system are taken into account. The effects of coatings and subsurface defects on the lubricant film thickness and fluid pressure profiles and elastic fields are analyzed in the cases presented. Stress intensity factors for the embedded cracks are obtained based on the solution and involved in the analysis. Highlights: Model for cracks and inclusions in layered materials under EHL contact. Interactions among solid contact bodies, fluid lubricant and structural defects. Solution of surface fluid lubrication pressure and subsurface stress field. Solution for stress intensity factors of cracks.